THE EFFECTIVENESS OF HERBAL MOSQUITO COILS "MORIZENA” AGAINST Aedes Aegypti DEATH - Susilowati, Rina Priastini; Darmanto, Win; Aminah, Nanik Siti (Indonesian Journal of Tropical and Infectious Disease, 2018)
It has been successfully found new herbal mosquito coils called "Morizena” made from Passiflora foetida leaf extract (40%), Chrysantemum cinerariaefolium flowers seed extract (40%), essential oils of  leaves-stems of Cymbopogon nardus (20%). The herbal mosquito coils are more effective to kill Aedes aegypti compared to commercial synthetic mosquito coils made from Transfluthrin. Treatment of exposure to herbal mosquito coils "Morizena” on Aedes aegypti for 8 hours/day with concentration 500 ppm (P1), 1000 ppm (P2), 2000 ppm (P3), 3000 ppm (P4), 4000 ppm (P5) and treatment of exposure to synthetic mosquito coils Transfluthrin 2500 ppm (K1) as a positive control, and without treatment of exposure to mosquito coils (K0) as a negative control. Experimental animals used were adult Ae. aegypti mosquito with 25 mosquitoes in each treatment. Experimental design used is one-way Anova test with linear regression to calculate its LC50 and LC90. The results of test to herbal mosquito coils "Morizena” given for 8 hours/day obtained mortality of Ae. aegypti by 92% to a concentration of 3000 ppm (P4) and 100% to a concentration of 4000 ppm (P5) and 100% for test to synthetic mosquito coils transfluthrin 2500 ppm (K1). Ae. aegypti LC50 and LC90 value for treatment of exposure to herbal mosquito coils "Morizena” are 999 ppm and 2977 ppm. Treatment of herbal mosquito coils "Morizena” with graded doses up to 4000 ppm and synthetic mosquito coils Transfluthrin 2500 ppm causing an increase in the enzyme acetylcholinesterase activity of Ae. aegypti. The conclusion is based on the Ae. aegypti  LC90 value is 2977 ppm, which means the effective dose of herbal mosquito coils "Morizena” to kill Ae. aegypti is 2977 ppm.